2021
DOI: 10.1016/j.molmet.2020.101117
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor 15 as a potential therapeutic for treating obesity

Abstract: Background Obesity is rapidly becoming one of the world's most critical health care concerns. Comorbidities accompanying excess weight include cardiovascular disease, diabetes, and certain cancers. These comorbidities result in greater hospitalization and other health care-related costs. Economic impacts are likely to be felt more acutely in developing countries, where obesity rates continue to rise and health care resources are already insufficient. Some of the more effective treatments are invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 84 publications
1
27
0
Order By: Relevance
“…Macrophage inhibitory cytokine 1 (MIC1; also known as GDF15) has gained attention as a target for obesity treatment 267 . GDF15 is a divergent member of the transforming growth factor-β (TGFβ) superfamily 267 .…”
Section: Novel and Emerging Obesity Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophage inhibitory cytokine 1 (MIC1; also known as GDF15) has gained attention as a target for obesity treatment 267 . GDF15 is a divergent member of the transforming growth factor-β (TGFβ) superfamily 267 .…”
Section: Novel and Emerging Obesity Therapiesmentioning
confidence: 99%
“…Macrophage inhibitory cytokine 1 (MIC1; also known as GDF15) has gained attention as a target for obesity treatment 267 . GDF15 is a divergent member of the transforming growth factor-β (TGFβ) superfamily 267 . Physiologically, GDF15 is expressed in multiple tissues at a low concentration, but increases in response to or association with tissue injury, cancer, metabolic disease, CVD and inflammation 267 , 268 .…”
Section: Novel and Emerging Obesity Therapiesmentioning
confidence: 99%
“…In brief, long-term treatment with hFGF21 analogues have been shown to reduce dyslipidaemia, enhance insulin sensitivity and reduce body weight in clinical trials (236). In addition, preclinical obesity studies have shown treatment with GDF15 decreases food intake and body weight (283). However, the benefit of augmented FGF21 and GDF15 treatment in reducing risk for severe IAV and SARS-CoV-2 infection in obesity has not yet been explored.…”
Section: Medical Interventions To Treat Obesity Induced-inflammationmentioning
confidence: 99%
“…Insulin C-peptide has been widely used as a proxy for secreted insulin due to its higher serum stability, yet it does appear to also have bioactivity of its own [63]. Some of the GFs have been demonstrated, at least in animal models of disease, to have potential for human therapy [64,65]. GDNF and the related family member Neurturin for the treatment of Parkinson's disease [66], Neurturin, as a potential key growth hormone in pancreas development, in diabetes, as well as GDF15 for obesity are particularly notable examples.…”
Section: Pro-domain Relevance In Medicine and Drug Discoverymentioning
confidence: 99%